1980
DOI: 10.1073/pnas.77.6.3700
|View full text |Cite
|
Sign up to set email alerts
|

Experimental animal model for mucopolysaccharidosis: suramin-induced glycosaminoglycan and sphingolipid accumulation in the rat.

Abstract: ABSTRACGIntracerebral injection of the trypanocidal drug suramin in rats caused the formation of membranous neuronal and neuroglial inclusions. Here we show that intravenous administration of suramin, 500 mg/kg, to 2-month-old rats causes a 5-to 8-fold increase of glycosaminoglycan concentration in the liver within 10 days and a 6-fold increase in urinary glycosaminoglycan excretion. The excess glycosaminoglycans consist of heparan sulfate and dermatan sulfate. Intracerebral injection of 250 Ag of suramin resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…In vivo, suramin has been shown to induce a GAG and lipid accumulation in rat tissue [9], including the rat incisor [17]. The present in vitro study also demonstrated an accumulation of GAG and lipids in lysosome-like vacuoles, as shown by the incorporation of radiosulphate and the immunostaining with MC22-33F of phosphatidylcholine and/or sphingomyelin.…”
Section: Effects Of Suramin On Zsso 4 Incorporationsupporting
confidence: 75%
See 1 more Smart Citation
“…In vivo, suramin has been shown to induce a GAG and lipid accumulation in rat tissue [9], including the rat incisor [17]. The present in vitro study also demonstrated an accumulation of GAG and lipids in lysosome-like vacuoles, as shown by the incorporation of radiosulphate and the immunostaining with MC22-33F of phosphatidylcholine and/or sphingomyelin.…”
Section: Effects Of Suramin On Zsso 4 Incorporationsupporting
confidence: 75%
“…The present in vitro study also demonstrated an accumulation of GAG and lipids in lysosome-like vacuoles, as shown by the incorporation of radiosulphate and the immunostaining with MC22-33F of phosphatidylcholine and/or sphingomyelin. This has been reported for rat tissues after a single administration of the drug [9,10]. The presence of lipid inclusions in the maturing presecretory ameloblasts is likely due to the inhibition by suramin of enzymes involved in lipid degradation.…”
Section: Effects Of Suramin On Zsso 4 Incorporationmentioning
confidence: 54%
“…Suramin, a polysulfonated naphtylurea with polyanionic character, used as an anti-trypanosomal drug, is taken into cells by endocytosis, accumulates in lysosomes, and inhibits phagosome-lysosome fusion (Hart and Young, 1975). Following intravenous administration, suramin induces an accumulation of GAGs and sphingolipids (Constantopoulos et al, 1980) due to inhibition of many lysosomal enzymes. The function of various ion pumps is inhibited (Moriyama and Nelson, 1988).…”
Section: (V) Pharmacological and Genetically Induced Pathologymentioning
confidence: 99%
“…The reduced catalytic activity of this endoglycosidase might be responsible for the accumulation of the respective types of glycosaminoglycans, in particular of chondroitin sulphate, dermatan sulphate and hyaluronate (4,8) possible Inhibition of the degradation of glycosaminoglycans due to a decrease of endoglycosidically active hyaluronate-4-glycanohydfolase; the former enzymes act mainly on oligosaccharides (34,35), and in the case of chondroitin sulphate and dermĂ€tan sulphate they act on the desulphated oligosaccharides at the non-reducing terminal (36). The important role of hyaluronate-4-glycanohydrolase in the catabolism of liver glycosaminoglycans is suggested by Constantopoulos et al (37) from studies with the trypanocidal drug suramin. In the presence of this drug the strong Inhibition of the enzyme is accompanied by an increase in the total glycosaminoglycan concentration in rat liver tissue.…”
Section: Discussionmentioning
confidence: 95%